Antimicrobial Activity of Proteus Bacteria Isolated From Raw Milk of Paonta Valley - Virender Singh; Leena Sharma; Rohini Kanta; Sheetal Sharma; Swati Chauhan; P.K. Chauhan. (International Journal of Pharma and Bio Sciences, 2010)
This study was carried out from 8th Mar 2007 to 8th Dec 2009. A total of 65 consecutive Proteus recovered during the study period in 360 milk samples of different area of Paonta valley, 40 isolates were ESBL producer and 25 isolates were non-ESBL producers. Detection of extended spectrum β-lactamase producing Proteus in raw milk and milks products was carried out by Kirby Bauer disc diffusion method, on Muller Hinton Agar. A susceptibility disk containing Piperacillin Tazobactum was placed as the inhibitor of β-lactamase in the center of the plate, Piperacillin were placed 30mm from the Piperacillin Tazobactum disk. Enhancement of zone of inhibition of disc of Piperacillin alone towards the disc containing Piperacillin Tazobactum, showing a figure of eight impression were considered as ESBL producer. Escherichia coli ATCC 25922 and K. pneumoniae ATCC 700603 were used as control strains. The prevalence of extended spectrum β-lactamase producing Proteus in raw milk and milks products of Paonta valley was 11%.